Enhanced transfer of terrestrially derived carbon to the atmosphere in a flooding event. Issue 1 (8th January 2013) - Bianchi, Thomas S.; Garcia‐Tigreros, Fenix; Yvon‐Lewis, Shari A.; Shields, Michael; Mills, Heath J.; Butman, David; Osburn, Christopher; Raymond, Peter; Shank, G. Christopher; DiMarco, Steven F.; Walker, Nan; Reese, Brandi Kiel; et al.
Abstract [1] Rising CO2 concentration in the atmosphere, global climate change, and the sustainability of the Earth's biosphere are great societal concerns for the 21st century. Global climate change has, in part, resulted in a higher frequency of flooding events, which allow for greater exchange between soil/plant litter and aquatic carbon pools. Here we demonstrate that the summer 2011 flood in the Mississippi River basin, caused by extreme precipitation events, resulted in a "flushing" of terrestrially derived dissolved organic carbon (TDOC) to the northern Gulf of Mexico. Data from the lower Atchafalaya and Mississippi rivers showed that the DOC flux to the northern Gulf of Mexico during this flood was significantly higher than in previous years. We also show that consumption of radiocarbon‐modern TDOC by bacteria in floodwaters in the lower Atchafalaya River and along the adjacent shelf contributed to northern Gulf shelf waters changing from a net sink to a net source of CO2 to the atmosphere in June and August 2011. This work shows that enhanced flooding, which may or may not be caused by climate change, can result in rapid losses of stored carbon in soils to the atmosphere via processes in aquatic ecosystems.